Urinary Beta-2Microglobulin: An Indicator of Renal Tubular Damage after Extracorporeal Shock Wave Lithotripsy - Nasseh, Hamidreza; Abdi, Sepideh; Roshani, Ali; Kazemnezhad, Ehsan (Urology Journal, 2016)
<!--[if gte mso 9]> <![endif]--> Purpose: This study aims to determine extracorporeal shock wave lithotripsy (ESWL)-induced renal tubular damageand the affecting factors by measuring urinary beta2microglobulin (β2M) excretion. Materials and Methods: This is a cross-sectional study conducted on 91 patients with renal stones who underwentESWL during 2012. Urinary beta2microglobulin was measured immediately before and after the procedure foreach patient and analyzed based on different variables to evaluate factors affecting ESWL-induced renal tubularinjury. Results: Mean ± SD urinary beta2-microglobulin values, before and after ESWL were 0.08 ± 0.07 and 0.22 ± 0.71mg/dL respectively, the average difference between which was equal to 0.14 ± 0.07 mg/dL. These figures exhibiteda 166.66% rise in the urinary β2M concentration after ESWL which was statistically significant (P < .001). Multivariateanalysis showed that hypertension (P = .05) and the history of ESWL (P = .02) were predictive factors ofhigher post-ESWL urinary beta2-microglobulin excretion. Conclusion: Urinary excretion of beta2-microglobulin increased significantly immediately after ESWL. Thesechanges could indicate that ESWL is a contributing factor to renal tubular damage. It also seems that in patientswith hypertension and a previous history of ESWL the likelihood of this injury is higher than others. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif";} --> <!--[endif] -->